2020
DOI: 10.2147/ndt.s218483
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Role of Cytokines in Predicting the Efficacy of Acute Stage Treatment in Patients with Schizophrenia</p>

Abstract: Purpose: Inflammatory response in schizophrenia (SCz) is related to its underlying pathological mechanism and might be significant in deciding a patient's prognosis. The current study aims to investigate the differences in the serum inflammation level between schizophrenic patients and healthy controls and identify inflammatory markers that can predict clinical therapeutic effects in early-stage SCz patients at the 6-month follow-up. Patients and Methods: In total, 71 subjects were recruited in this study, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…These findings suggest that pro-inflammatory cytokines are significantly stimulated in schizophrenia subjects regardless of obvious inflammation and that anti-inflammatory strategies using diet and drugs may be utilized as a potential adjuvant therapy. In fact, some anti-psychotic drugs (e.g., clozapine, olanzapine, and risperidone) reduced the levels of pro-inflammatory cytokines including IL-8 and IL-12 in first episode and relapse state schizophrenia patients [ 36 37 ]. Although there has been inconsistency in alterations of cytokine levels and types of affected cytokines, several pro-inflammatory cytokines were relatively higher in schizophrenia subjects compared with controls, which was suppressed by the treatment of anti-psychotic drugs, resulting in alleviation of symptoms of schizophrenia.…”
Section: Inflammation and Schizophreniamentioning
confidence: 99%
“…These findings suggest that pro-inflammatory cytokines are significantly stimulated in schizophrenia subjects regardless of obvious inflammation and that anti-inflammatory strategies using diet and drugs may be utilized as a potential adjuvant therapy. In fact, some anti-psychotic drugs (e.g., clozapine, olanzapine, and risperidone) reduced the levels of pro-inflammatory cytokines including IL-8 and IL-12 in first episode and relapse state schizophrenia patients [ 36 37 ]. Although there has been inconsistency in alterations of cytokine levels and types of affected cytokines, several pro-inflammatory cytokines were relatively higher in schizophrenia subjects compared with controls, which was suppressed by the treatment of anti-psychotic drugs, resulting in alleviation of symptoms of schizophrenia.…”
Section: Inflammation and Schizophreniamentioning
confidence: 99%
“…Stress response secondary to inflammation sensitizes and primes the microglial cells, thereby increasing the release of pro-inflammatory cytokines. Patients with schizophrenia have higher levels of pro-inflammatory cytokines than do healthy controls [47,48]. In addition, positron emission tomography studies of receptors (PK11195 and DAA1106) have demonstrated that the activation of microglial receptors is associated with neuronal damage in patients with recent-onset schizophrenia [43,49].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, they justified this association by increasing the production of T cells following a patient suffering from depression. 6 However, Maes et al showed that serum levels of IL-2 and serum levels of IL-2 receptors increase in patients with major depression. Their study evaluated patients who were in the final phase of treatment, and their results also showed an increase in serum IL-6 levels.…”
Section: Interleukin-2 Status In Major Depressionmentioning
confidence: 99%
“…5 On the other hand, researchers believe that chronic inflammation can be one of the causes of depression. 6 Depression is a mental disorder that affects 15 million people a year. Depression is a disorder characterized by mood swings and includes feelings of sadness ranging from mild frustration to severe despair.…”
Section: Introductionmentioning
confidence: 99%